Estudio de factibilidad de implementación de un sistema solar fotovoltaico como solución alternativa para la alimentación eléctrica del pozo CVMM-1 con levantamiento artificial con bomba de cavidades progresivas ubicado en un campo en la Cuenca del Valle Medio del Magdalena (2024)
The present degree work is focused on carrying out a feasibility study for the implementation of a photovoltaic solar system as an alternative solution to electrically energize a pumping unit with progressive cavities located in a La Cira Infantas field, in the Middle Valley Basin. of the Magdalena. To do this, the potential zones of solar radiation in the Basin (most representative maximum peaks) were identified by using the IDEAM Radiation Atlas of Colombia tool. Next, the fundamental criteria were defined for the selection of the CVMM-1 well with the purpose of coupling the solar photovoltaic system. Subsequently, the energy consumption per hour during the day of the pumping unit with progressive cavities was determined. Additionally, the sizing of all the elements that make up the solar photovoltaic system adapted to the energy demand of the pumping unit was carried out, by calculating the number of solar panels, batteries, inverters and regulators. Finally, the economic analysis of the project was carried out to determine its profitability after 20 years.